2022
DOI: 10.1088/2058-8585/ac4bb1
|View full text |Cite
|
Sign up to set email alerts
|

Printed zinc tin oxide diodes: from combustion synthesis to large-scale manufacturing

Abstract: Printed metal oxide devices have been widely desired in flexible electronic applications to allow direct integration on foils and to reduce electronic waste and associated costs. Especially, semiconductor devices made from non-critical raw materials, such as Zn, Sn (and not, for example, In), have gained much interest. Despite considerable progress in the field, the upscale requirements from lab to fab scale to produce these materials and devices remain a challenge. In this work, we report the importance of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…As a result, the coating morphology was tuned from smooth to porous thin films, respectively, which allows the TE to be tailored for different final applications. Finally, as a proof of concept, a TH with a 50 × 50 mm 2 size was tested as a defroster (down to −21 °C) showing a highly reproducible heating performance (up to 90 °C at 6 V) and stability for 12 h. Such results are very promising for the low-cost, easily scalable, large-scale manufacturing of transparent heaters, considering the recent advances on roll-to-roll and printing techniques of metals and metal oxides …”
Section: Introductionmentioning
confidence: 99%
“…As a result, the coating morphology was tuned from smooth to porous thin films, respectively, which allows the TE to be tailored for different final applications. Finally, as a proof of concept, a TH with a 50 × 50 mm 2 size was tested as a defroster (down to −21 °C) showing a highly reproducible heating performance (up to 90 °C at 6 V) and stability for 12 h. Such results are very promising for the low-cost, easily scalable, large-scale manufacturing of transparent heaters, considering the recent advances on roll-to-roll and printing techniques of metals and metal oxides …”
Section: Introductionmentioning
confidence: 99%
“…[ 38 ] In another study, printed Ag contacts on ZTO were reported to show unstable switching characteristics that were explained by Ag ion migration into the oxide layer. [ 165 ] It has also been reported that a relatively good contact into In 2 O 3 semiconductor with small hysteresis can be achieved after annealing at much higher temperatures than what is specified for the Ag ink by the material provider. [ 43 ] The improved properties were suspected to be due to enhanced field emission caused by Ag‐migration spikes in the semiconductor during the annealing step.…”
Section: Methodsmentioning
confidence: 99%
“…The doping profiles between untreated and plasma treated were compared and the processes that is happening at the p‐n junctions were hypothesized. Given the relevance of ZTO diodes to the state of the art and even flexible electronic devices such as those demonstrated by Carlos et al., [ 16 ] we believe that the C–V analysis can highlight the differences in performance of plasma‐treated and untreated diodes which are difficult to observe in I–V analysis. In addition, C–V analysis allows extraction of charge density profiles, which is a measure of the defect state density that led to intrinsic doping, which in turn plays a significant role in electronic device characteristics.…”
Section: Introductionmentioning
confidence: 92%
“…[10][11][12][13][14][15] Carlos et al has also reported that their indium-tin oxide (ITO)/ZTO/poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) Schottky diodes fabricated in the pilot-scale roll-to-roll (R2R) printing line exhibited rectification ratio of 20 without plasma treatment, but showed rectification of up to 1000 after plasma treatment of all 3 ZTO layers. [16] Different metal contact deposition methods and the order of deposition of semiconductors and metals have a strong impact on the performance of the device due to oxidation or reduction processes at the interface. Oxygen treatment of the surface of the metal oxide or certain metal contacts before the deposition of the next layer of oxide can benefit the formation of an interface by chemically stabilizing the contact interface, removing any highly conductive surface accumulation layer or reducing any interfacial trap states.…”
mentioning
confidence: 99%